Отглагольные имена существительные с суффиксом -(е)нье, -(е)ние в Московском переводе-редакции Литовского Статута - Судавичене, Л. (Kalbotyra, 1972)
The article deals with the semantics and usage of nouns with the suffix (-e)ньe, -(e)ниe in written monuments. The material under analysis was collected from LSMV and LS and checked in Russian, Polish and Byelorussian dictionaries. The comparison of the above mentioned nouns in LSMV and LS shows that the pattern of word building VS and PVS was common to the Russian and Byelorussian languages. The suffix -ньe is more characteristic of the Byelorussian language, while in the Russian language alongside with -ньe its variant -ниe is used. Nouns with the suffix -ниe are few in number and, as a rule, they have originated from old Slav. Though verbs form aspective pairs (oбжечь-обжигать; заступить-заступать), nouns with the mentioned suffix are formed only from one stem (cf. обжиганье, заступленье, etc.).